Profitability and growth topology analysis of unilevel-type of network marketing structures - Daquis, John Carlo P. (Philippine Statistician, 2013)
This study analyzes a type of multilevel marketing (MLM) structure through a simulation study of MLM systems. In unilevel MLM, distributors earn from both sales from direct selling and commissions from recruitment of downlines. Several distributional assumptions were made in constructing the system, such as the use of the uniform, Bernoulli, and Poisson distributions. Member income is measured based on commission from recruit pay-ins in their downlines and income from direct selling. Based on the simulated unilevel MLM structures, the fundamental behavior of a unilevel MLM is captured and analyzed in terms of its network growth topology and profitability.